"Ordinance No. 29: Concerning the Carrying of Concealed Weapons." The Nashville Journal, March 26, 1880, p. 4. Adopted March 24, 1880. Volume 18, Number 12. (Nashville, Illinois). - (:unkn) unknown (General Publisher, 1880)
Prohibited concealed carry of any pistol, slung-shot, cross knuckles of lead, brass, or other metal, Bowie-knife, dirk, dagger, or any knife resembling a Bowie-knife, or any other dangerous or deadly weapon, instrument, or thing within the limits of the city. Violators fined not less than twenty nor more than two hundred dollars and cost of suit for each offense.
--
Keywords: CARRY - CONCEALED